Technology Learning Integration in Kindergarten: From Play to Programming with ScratchJr - Widya Dwi Hardiyanti; Prayitno Prayitno (Universitas Sebelas Maret, 2026)
The rapid advancement of 21st-century technology necessitates that young children become not only digital consumers but also develop 5C (Creative thinking, Critical thinking, Communication, Collaboration, and Computational thinking). One innovative approach to fostering these abilities is through early exposure to programming. However, in the context of Surakarta, Indonesia, programming learning has not yet been widely or systematically implemented in kindergarten. This study aims to explore the programming practices of children aged 5–6 using ScratchJr, a visual programming application designed specifically for young learners. A qualitative case study method was employed, involving 20 children from a Kindergarten in Surakarta. Data were gathered through direct observation and documentation of children's project outcomes during individual 30-45-minute sessions. Findings revealed that the majority of children were capable of exploring ScratchJr features and constructing basic programming sequences to create animated story projects. The children exhibited high levels of engagement, curiosity, and creativity throughout the activity. Many demonstrated an understanding of debugging and symbolic thinking. Moreover, ScratchJr served as an effective medium to support artistic expression, indicating the development of creativity and cognitive growth through interactive digital experiences. In conclusion, programming activities facilitated by ScratchJr offer a developmentally appropriate and engaging approach to enhancing computational thinking and creativity. The study recommends increased investment in digital infrastructure and professional development for educators to enable the broader implementation of programming in kindergarten for preparing young learners to thrive in an increasingly digital global world.